The effect of anesthetics on carotenoid pigmentation and behavior in Arctic char (Salvelinus alpinus) - Backström, Tobias; Heynen, Martina; Brännäs, Eva; Nilsson, Jan; Magnhagen, Carin (2015)
Status of individual animals is often shown in pigmentation. For instance, stress responsiveness is associated with melanin-based pigmentation in vertebrates in general. This pattern is evident in Atlantic salmon (Salmo salar) and rainbow trout (Oncorhynchus mykiss), with melanin-based spots indicating stress coping style. Arctic char (Salvelinus alpinus) differ from other salmonids in pigmentation but have an association between carotenoid-based pigmentation and stress coping style. These pigmentation differences could be used as a fast and simple tool for improving breeding programs. However, the procedure for photographing individuals is stressful. Therefore, we wanted to investigate if 3 common inhalation anesthetics could be used to reduce the stress involved in the procedure compared to a no-anesthetics group. Behavior was also monitored during the anesthetization. All 3 anesthetics (Aquacalm, Benzocaine, and MS-222) differed in pigmentation compared to the no-anesthetics group by having a higher number of spots. In the anesthetic treatments as well as the no-anesthetics group, the fish had elevated plasma cortisol levels. In fact, the no-anesthetics group had higher cortisol than treated fish. This was probably because of procedural differences such as time affecting the stress response. Furthermore, in a long-term experiment, all fish survived and had similar condition factors 1 week after photographing as before. Therefore, the method for photographing Arctic char is deemed safe and could be used as a tool for estimating stress coping style, but careful planning is needed for experiments using it